Experimental Methods in Psychology and Cognitive and Affective Neuroscience - Habekost, Thomas; Nielsen, Julie Hassing (Politik, 2014)
Laboratory experiments have always been important in psychology and are as commonly used today as ever due to the dominating position of cognitive research in international psychology. is trend has been fur- ther strengthened by recent developments in cognitive neuroscience, where experimental studies are central. Recently, experimental studies within the eld of a ective neuroscience have also received attention. Not- withstanding, experimental methods remain controversial also in psychology, and one should carefully weigh their advantages against their drawbacks. is article provides an introduction to experimental psychology, including basic principles and illustrative examples. e article focuses on the experimental method in its purest form, the controlled laboratory study, and discusses the value of this scienti c approach with regard to ecological validity and socio-cultural factors. Furthermore, the article describes the use of experiments within cognitive and a ective neuroscience as well as the inherent challenges of individual versus social perspectives when conducting micro level laboratory experiments.